Ultra-Processed Food Availability and Sociodemographic Associated Factors in a Brazilian Municipality - Serafim, Patricia; Borges, Camila Aparecida; Cabral-Miranda, William; Jaime, Patricia Constante (Frontiers in Nutrition, 2022)
The availability of ultra-processed foods in a municipality tends to be related with different type of food retailers and their location in the territory, besides social, economic, and demographic factors. The aim of this paper is to evaluate the availability of ultra-processed foods according to different type of food retailers and sociodemographic factors. This is a cross-sectional observational study carried out with audit data from food retailers in the municipality of Jundiaí-SP. Using a validated instrument, data on the availability of 18 types of ultra-processed foods were used to create a score of ultra-processed foods, ranging from 0 to 100 points, and five subscore referring to the ultra-processed food subgroups. Descriptive statistics and means comparison tests were performed to verify differences in the ultra-processed food availability score, according to food retail type, household income, number of household members, and percentage of black, brown, yellow, indigenous population in the census tract in which food retailers were located. Geo-referenced maps were used to characterize the score of ultra-processed in the territory, according to sociodemographic variables. A total of 649 food retailers were analyzed, most of which were classified as neighborhood markets (25.4%). The supermarkets were the category with the highest ultra-processed foods availability score. Among the subgroups of ultra-processed foods analyzed, candies, soft drinks, and snacks were available in 60% of the food retailers. Higher ultra-processed foods availability score was observed in regions with lower income, higher percentage of black, brown, yellow and indigenous population, and a higher number of members per household. The findings show that the greater availability of ultra-processed foods is related to supermarkets and markets, and regions of greater social vulnerability, which can put this population at nutritional risk.